ORGANIZATIONAL AND PEDAGOGICAL CONDITIONS FOR TRAINING FUTURE BACHELORS OF PSYCHOLOGY FOR EENLIGHTENMENT OF THE PUBLIC - Sadykina, Alyona (European Journal of Interdisciplinary Issues, 2024)
The effectiveness of forming the readiness of future bachelors of psychology for enlightenment activities involves the determination of a number of organizational and pedagogical conditions. In modern pedagogical studies, researchers often use the concept of “organizational and pedagogical conditions” as a factor of influence on the educational process of training future specialists in higher educational institutions and reveal its essence in different contexts. However, the organizational and pedagogical conditions they identify are not always relevant, and in addition, their list does not always include the actual organizational and pedagogical conditions. This is due to the subjectivity of the researcher and the lack of theoretical training. Therefore, it is necessary to find out what is involved in the content of this concept, to identify a list of organizational and pedagogical conditions for the formation of future bachelors of psychology’s readiness for enlightenment activities, and to justify the feasibility of their choice. The purpose of the research is to identify, characterize and substantiate certain organizational and pedagogical conditions for training future bachelors of psychology for enlightenment activities. The following methods were used in the research: the method of analysis for studying the scientific source base on the specified issues; methods of synthesis, theoretical generalization and comparison for highlighting the organizational and pedagogical conditions for preparing future bachelors of psychology for enlightenment activities and their substantiation; the method of inference for formulating conclusions. The essence of the concepts of “conditions” and “organizational and pedagogical conditions” has been defined. The organizational and pedagogical conditions for the formation of future psychologists’ readiness for enlightenment activities are determined: 1) updating the content of professionally oriented disciplines taking into account the specifics of psychological education; 2) active participation of future bachelors of psychology in educationally oriented extracurricular activities; 3) formation of a positive motivation for educational activities in future bachelors; 4) formation of a holistic scientific and psychological worldview in future bachelors of psychology; 5) creation of a reflective environment. Effective preparation of future bachelors of psychology for enlightenment activities involves the comprehensive implementation of the proposed organizational and pedagogical conditions.